Specificity of uracil uptake in Neurospora crassa. - Dalke, P (1979)
The specificity of uracil uptake was investigated in germinating wild-type conidia of Neurospora crassa. From comparative inhibition studies, several generalizations concerning the specificity of uracil uptake can be made. (i) The tautomeric forms of uracil analogs is an important determinant of recognition by the uptake system. (ii) Substituents at the 5 position of the pyrimidine ring may impose steric constraints on binding. (iii) The presence of a negative charge results in the loss of recognition. (iv) The double bond between the 5 and 6 carbons appears to be important for recognition. (v) Purine bases do not inhibit uracil uptake. Crude extracts of the transport-deficient mutant strain uc-5 pyr-1 were shown to have uridine 5'-monophosphate pyrophosphorylase activity comparable to that of the wild-type strain, suggesting that uracil uptake in Neurospora does not occur by a group translocation mechanism involving phosphoribosylation. Specificity studies of uridine 5'-monophosphate pyrophosphorylase indicated that phosphoribosylation was not an important determinant of the specificity of uracil uptake.